Time delay controller for the position control of a MRI-compatible pneumatic actuation with long supply lines - Franco,E; Ristic,M (IEEE, 2014)
Pneumatic actuation with long supply lines is widely employed in robotic devices operating in the Magnetic Resonance Imaging (MRI) environment because it produces minimum alteration to the magnetic field. However the high friction of the cylinders and the delay introduced by the pipes make accurate position control challenging. This work presents design and control of an MRI-compatible pneumatic actuation that employs a commercially available, plastic cylinder and long supply lines connecting with the control hardware located outside the magnet room. The system has been designed to actuate a MRI-compatible needle-guiding robot intended for MRI-guided intervention of liver tumors. Accurate position control is achieved with a new Time Delay Control (TDC) scheme that includes a saturation function. The controller requires limited knowledge of the system's parameters and does not rely on pressure or force measurements. Simulation results and experiments demonstrate the advantages of the proposed controller over existing TDC schemes. The MRI-compatibility of the pneumatic actuation is verified in a 3T MRI scanner.